2011
DOI: 10.3109/s10165-010-0362-y
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictive factors for malignancies in 136 Japanese patients with dermatomyositis, polymyositis and clinically amyopathic dermatomyositis

Abstract: The aim of this study was to define the standardized incidence ratio (SIR) of malignancy and the potential risk factors of concomitant malignancies in patients with inflammatory myopathies, including clinically amyopathic dermatomyositis (CADM). A total of 145 patients diagnosed with either dermatomyositis/polymyositis (DM/PM) or CADM at our institute between 1984 and 2002 were enrolled in the study. The demographic, clinical and laboratory features of the patients at the time of DM/PM or CADM diagnosis were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 10 publications
6
32
0
5
Order By: Relevance
“…Azuma et al reported that three of 10 Japanese patients with CADM were found to have malignancy. 25 Another study in Hong Kong reported five of six patients with CADM developed an associated malignancy. 24 A retrospective cohort study of 746 patients with DM at the Mayo Clinic identified 37 cases of CADM based on the classifications of Stonecipher et al, five of whom had an associated malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Azuma et al reported that three of 10 Japanese patients with CADM were found to have malignancy. 25 Another study in Hong Kong reported five of six patients with CADM developed an associated malignancy. 24 A retrospective cohort study of 746 patients with DM at the Mayo Clinic identified 37 cases of CADM based on the classifications of Stonecipher et al, five of whom had an associated malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Azuma et al . reported that three of 10 Japanese patients with CADM were found to have malignancy . Another study in Hong Kong reported five of six patients with CADM developed an associated malignancy .…”
Section: Discussionmentioning
confidence: 99%
“…Factors associated with malignancies in patients with IIM have included cutaneous necrosis, low serum CK concentration, increased ESR, decreased serum albumin concentration, poikiloderma, dysphagia, older age, male sex, absence of arthralgia, and absence of ILD 10,11,12,18,19,20 . Most of the factors we found associated with malignancy in patients with IIM had been identified previously.…”
Section: Discussionmentioning
confidence: 99%
“…Magasabb életkor a myositis diagnózisakor, férfi nem, fogyás, magas láz, thrombotikus folyamatok és szövődményeik jelenléte gyakoribb tumorral társult myositis esetében. Laboratóriumi vizsgálatok eredményei közül a myositis kezdetén jelentkező magas kreatin-kináz (CK) és Westergren (We) értékek jellegzetesek a CAM esetekben [2,8,11,15]…”
Section: öSszefoglalásunclassified
“…Bizonyított az idiopathiás inflammatorikus myopathiák daganatos megbetegedésekkel való fokozott társulási hajlama [6][7][8][9][10][11][12]21]. A tumorral társuló myositis a legrosszabb prognózisú myositis alcsoport, a betegség prognózisát elsősorban a daganatos betegség stádiuma határozza meg.…”
Section: Megbeszélésunclassified